Pemanfaatan Citra Satelit dan Foto Udara untuk Pemetaan Pola Ruang di Desa Bunga Jadi Kecamatan Muara Kaman - Muhammad Alfianur; Andi Baso Sofyan A. P.; Dawamul Arifin; Shabri Indra Suryalfihra; Siti Hutami Adianengsih Gaffar (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2024)
The spatial pattern mapping in village areas plays a crucial role in sustainable village planning and development. The objective of this study is to produce a spatial pattern map of Bunga Jadi Village, located in Muara Kaman Sub-district, Kutai Kartanegara Regency, and to identify the distribution of spatial patterns within the village. The results of the spatial pattern mapping in Bunga Jadi Village indicate that the protected area covers 1,106.72 hectares, or approximately 21.04% of the total area, while the cultivation area covers 4,152.62 hectares, or around 78.96% of the total area. The functional classification of areas in Bunga Jadi Village includes forest areas, peatland forests, green open spaces (RTH), business/trade and service areas, mining areas, and the most prominent potential area in the village, which is the plantation area, with a total area of 5,259.34 hectares.